(3CSQGQ GdedchJs - (3YHGS bdj Hf ejQRG eMeO NGf GdKGfj GdHGchj GdbOSjs
(3ChdgG (B:s
(3GdMeO ddg GdPi Ydi GdYQT ESJhi hHYO , ajbhd Ef ai Yde GdgjFI bGYOJjf , EMOGgeG dHWdjehS GdQhei eHfjI Ydi Schf GdCQV hOhQ GdTeS YdjgG s
(3BNQgG (B:s
(3hjXgQ ef Pdc Cfg dGJNdh ObjbI hdGKGfjI ef Cf JJchf hJafi ajgG YOI OhGFQ TeSjI hai GdMOjK Cfg deG SFd ehSi SHMGf QHc QH GdYRI YeG jUahf hSdGe Ydi GdeQSdjf s
(3Cdag GdeDda ddSdWGf YHO GdeLjO NGf SfI (B1262(3g`s
(3HChdgG Jedc eDQN SfI (B1325(3g`s
(3HgG fXGe GdJYbjHIs
(3HgG LOGhd s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
Keywords: (3Gdadcs